Effects of nitrogen deposition on the rhizosphere nitrogen-fixing bacterial community structure and assembly mechanisms in Camellia oleifera plantations - Liu, Caixia; He, Zhilong; Chen, Yongzhong; Xu, Yanming; Tang, Wei; Chen, Longsheng (Frontiers in Microbiology, 2024)
Increased nitrogen deposition is a key feature of global climate change, however, its effects on the structure and assembling mechanisms of the nitrogen-fixing bacteria present at the root surface remain to be elucidated. In this pursuit, we used NH4NO3 to simulate nitrogen deposition in a 10-year-old Camellia oleifera plantation, and set up four deposition treatments, including control N0 (0 kg N hm−2 a−1), low nitrogen N20 (20 kg N hm−2 a−1), medium nitrogen N40 (40 kg N hm−2 a−1) and high nitrogen N160 (160 kg N hm−2 a−1). The results showed that nitrogen deposition affected the soil nitrogen content and the structure of the nitrogen-fixing bacterial community. Low nitrogen deposition was conducive for nitrogen fixation in mature C. oleifera plantation. With increasing nitrogen deposition, the dominant soil nitrogen-fixing bacterial community shifted from Desulfobulbaceae to Bradyrhizobium. When nitrogen deposition was below 160 kg N hm−2 a−1, the soil organic matter content, total nitrogen content, nitrate nitrogen content, ammonium nitrogen content, urease activity, soil pH and nitrate reductase activity influenced the composition of the nitrogen-fixing bacterial community, but the stochastic process remained the dominant factor. The results indicate that the strains of Bradyrhizobium japonicum and Bradyrhizobium sp. ORS 285 can be used as indicator species for excessive nitrogen deposition.